2018
DOI: 10.30958/ajmmc.4.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Uses and Gratifications of Online News among Young Adults in Bahrain

Abstract: This study examines the use of local and Arab news websites among young adults in Bahrain. It identifies the patterns of use, the reasons of choices, and the factors that influence these choices and highlights the potential difficulties, if any, preventing users from finding gratifications in their news practices. A survey was administered to a random sample of 522 Bahraini young adults aged 18 to 29 years to achieve the objectives of the study. The study found that online news consumption by young adults in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…The U&G theory was originally developed in the research of Paul Lazarsfeld in 1940 concerning to radio listeners. The theory is then applied to the problem of the mass media used to explore why audiences choose certain media (Alsridi, 2018;Gogan, Zhang, & Matemba, 2018;So, 2012). Subsequently, academics and researchers began to research U&G theory and its application in various types of mass media (Kearney, 2018;Kircaburun, Alhabash, Tosuntaş, & Griffiths, 2018).…”
Section: Theory Of Uses and Gratificationmentioning
confidence: 99%
“…The U&G theory was originally developed in the research of Paul Lazarsfeld in 1940 concerning to radio listeners. The theory is then applied to the problem of the mass media used to explore why audiences choose certain media (Alsridi, 2018;Gogan, Zhang, & Matemba, 2018;So, 2012). Subsequently, academics and researchers began to research U&G theory and its application in various types of mass media (Kearney, 2018;Kircaburun, Alhabash, Tosuntaş, & Griffiths, 2018).…”
Section: Theory Of Uses and Gratificationmentioning
confidence: 99%
“…With 5 billion of mobile internet users (Sivakumaran & Iacopino, 2018). The Internet is the first source to get the latest news (67%), and young people prefer mobile phone as the greatest tool to get breaking news, the majority of respondents (72 %) confirmed that they access to news via mobile applications (Alsridi, 2018).…”
Section: Literature Review 21 Mobile Newsmentioning
confidence: 99%
“…Mobile news' adoption has followed the rapid adoption of mobile devices. (89 %) of users are consuming news by mobile, particularly, young people prefer mobile phone as the greatest tool to get breaking news, the majority of respondents (72 %) confirmed that they access to news via mobile applications (Alsridi, 2018). The ability to access to news while on the go is a crucial factor for mobile news consumption (Schmitz Weiss, 2018).…”
mentioning
confidence: 99%
“…In the Kingdom of Bahrain, a previous study about the uses and gratifications of online news among young adults (Alsridi, 2018), shows that The local news websites have a high percentage of use, although they do not rely on a strategy for editing or providing digital services other than the paper version (Dagiral & Parasie, 2010).…”
Section: Introduction mentioning
confidence: 99%